Forced vibrations of an anisotropic rectangular plate with piezosensors with account for shear deformations - Karnaukhov, V.G.; Kozlov, V. I.; Karnaukhova, T.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
Refined Timoshenko’ model of vibrations of thin-walled viscoelastic anisotropic plates with distributed transversally isotropic sensors is presented. The simple formula for the sensor indications is obtained. The influence of the shear deformations on the indicators is investigated.